THE ROLE OF SOCIAL ENVIRONMENT IN SHAPING ADOLESCENTS’ FINANCIAL MANAGEMENT CAPABILITIES - Rizka, Chelsea; Marsofiyati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to determine the effect of social environment on financial management skills in adolescents. This study uses a quantitative approach with Mann Whitney analysis. The population of this study were adolescents aged 15 to 22 years with random sampling techniques. Primary data were collected through a Likert-scale questionnaire. The results showed that the social environment has a significant effect on adolescents' ability to manage finances. Based on the results of the Mann Whitney test, the value of Asymp.Sig. (2-tailed) <0.05, so H0 is rejected. Therefore, it can be concluded that there is an influence of the social environment on the financial management skills. This study concludes that family, friends, and social media as part of the social environment play an important role in building adolescents' ability to manage finances. Suggestions for future research are to add other relevant variables and use qualitative methods to obtain more detailed data.